The essay genre in Serbian musicography of the first half of the 20th century: the case of the Serbian Literary magazine - Vasić, Aleksandar (Muzikološki zbornik, 2010)
From 1903 until 1941 twenty three essays on European music were published in the Serbian Literary Magazine, on the subject of music classicism, romanticism and modernism. This article aims to present a survey, a typology and the analysis of those essays.
Keywords: 20.st.; 20th century; glasbena esejistika; Lazarević, Branko, 1883-1968; Milojević, Miloje, 1884-1946; music essayistic; Pavlović, Stevan K.; Serbia; Srbija; Srpski književni glasnik (periodika)